2016
DOI: 10.1080/15248372.2015.1086772
|View full text |Cite
|
Sign up to set email alerts
|

Multiracial Children’s and Adults’ Categorizations of Multiracial Individuals

Abstract: Research has explored how multiracial individuals are categorized by monoracial individuals, but has not yet explored how they are categorized by multiracial individuals themselves. We examined how multiracial children (4-9 years) and adults categorized multiracial targets (presented with and without parentage information). When parentage information was provided, multiracial targets were more likely to be categorized as neither wholly black nor wholly white. However, both multiracial adults and children more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Moreover, Black children were categorized as most Black, followed by Multiracial children, then White children, suggesting that Multiracial children were seen as not exclusively White or exclusively Black, but somewhere in between and with a tendency toward Black. These data are consistent with past research showing a Black-categorization bias when categorizing Multiracial adults (Ho et al, 2011;Peery & Bodenhausen, 2008) and children (Hirschfeld, 1995;, 2017, and therefore demonstrate further a consistent and highly replicable pattern of Multiracial individuals being categorized by others as members of their minority groups. We also found that categorization judgments were influenced by both participant race and children's emotional expressions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, Black children were categorized as most Black, followed by Multiracial children, then White children, suggesting that Multiracial children were seen as not exclusively White or exclusively Black, but somewhere in between and with a tendency toward Black. These data are consistent with past research showing a Black-categorization bias when categorizing Multiracial adults (Ho et al, 2011;Peery & Bodenhausen, 2008) and children (Hirschfeld, 1995;, 2017, and therefore demonstrate further a consistent and highly replicable pattern of Multiracial individuals being categorized by others as members of their minority groups. We also found that categorization judgments were influenced by both participant race and children's emotional expressions.…”
Section: Discussionsupporting
confidence: 90%
“…In conclusion, Multiracial children (ages 4 to 6), like Multiracial adults in previous research, were perceived as more Black than White (see also , 2017. Yet, Multiracial children, unlike Multiracial adults in previous research, were not categorized differently as a function of their emotional expressions, which could have stemmed from children being perceived as less threatening than adults (Goff et al, 2014), thereby reducing an angry = Black or an angry = outgroup bias.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Americans continue to apply hypodescent to Black‐White people today (Chen, Couto, Sacco, & Dunham, , Experiment 1; Ho, Kteily, & Chen, ; Ho, Sidanius, Cuddy, & Banaji, ; Ho, Sidanius, Levin, & Banaji, ; Noyes & Keil, , Experiment 4; Peery & Bodenhausen, , Experiment 1; Roberts & Gelman, , ). There are dispositional and situational factors that impact the likelihood that perceivers do so.…”
Section: Heuristics and Biases In Applying Monoracial Categories To Mmentioning
confidence: 99%
“…U.S. childrenare more likely than Israeli children to develop the concept that race is objective, thus indicating cross-cultural variation in racial essentialism (Diesendruck, Goldfein-Elbaz, Rhodes, Gelman, & Neumark, 2013). Moreover, the extent to which children categorize Multiracial children into different "kinds" of people varies as a function of their age, race, and experiences with inter-group contact (Roberts & Gelman, 2015;Roberts & Gelman, 2016a).…”
Section: Introductionmentioning
confidence: 99%